Two new steroidal tetraglycosides from the rhizomes of Smilacina atropurpurea - Ying Zhang; Haizhou Li; Chongren Yang; Yingjun Zhang (Elsevier, 2013)
Smilacina atropurpurea (family Convallariaceae) is a perennial herb used medicinally for the treatment of lung ailments, rheumatism, menstrual disorders, and cuts and bruises, by the local people of its growing areas in southwest China. The tender aerial part has also been used as a wild vegetable by Lisu, Naxi and Tibetan people. Chemical analysis of the rhizomes of this plant has allowed us to isolate two new minor steroidal tetraglycosides, specifically atropurosides H (1) and I (2), by repeated column chromatography over silica gel and reversed phase silica. The structures were determined to be (25R,S)-12β-hydroxy-spirost-5-ene-3β-yl-O-β-D-glucopyranosyl-(1→2)-[β-D-xylopyranosyl-(1→3)]-β-D-glucopyranosyl-(1→4)-β-D-galactopyranoside (1) and (25S)-5α-spirost-17α-hydroxy-3β-yl-O-β-D-glucopyranosyl-(1→2)-[β-D-xylopyranosyl-(1→3)]-β-D-glucopyranosyl-(1→4)-β-D-galacto pyranoside (2), respectively, on the basis of detailed spectroscopic analysis including 1D and 2D NMR techniques.